A 3D platform for the morphology modulation of materials: first principles calculations on the thermodynamic stability and surface structure of metal oxides: Co3O4, α-Fe2O3, and In2O3. (12th January 2016) - Ferrer, M M; Gouveia, A F; Gracia, L; Longo, E; Andrés, J
Abstract: Essentially, the exposed crystal planes of a given material, which primarily determine their morphology, tremendously affect its behavior. First principle calculations, based on the Wulff construction model and broken bonding density index, have been performed to calculate the equilibrium and their transformations for different metal oxides: Co3 O4, α -Fe2 O3, and In2 O3 . Present results point out that starting by surface thermodynamics is a helpful approach to predict and assess the morphology transformations of these materials. These complete set of morphologies may serve as a guide for researchers, when analyzing the images from electron microscopies, to gain further understanding of how to control crystal shape synthetically by tuning the surface chemistry and by controlling the relative values of surface energies.